Sweet's syndrome: A reaction to non-tuberculous mycobacterial infections - Chanisada Tuchinda (2018)
Sweet's syndrome has been reported to be associated with many underlying conditions; such as non-tuberculous mycobacterial infections (NTMI). In the literature, only twelve patents with Sweet's syndrome in association with NTMI have been reported (most of the patients were from Thailand). Here, the authors report six more patients who developed Sweet's syndrome as a reaction to NTMI. Four patients had Mycobacterium chelonae/abscessus group infection; one patient had been infected with Mycobacterium avium complex first and became infected with M. chelonae/abscessus group 17 months later; and, the other one had Mycobacterium fortuitum infection. In each patient, the skin lesions of Sweet's syndrome relapsed many times while they still had NTMI, and these lesions usually responded well to short courses of systemic steroids without any deterioration of NTMI.